Conserved and Divergent Aspects of Plasticity and Sexual Dimorphism in Wing Size and Shape in Three Diptera - Reis, Micael; Siomava, Natalia; Wimmer, Ernst A.; Posnien, Nico (Frontiers in Ecology and Evolution, 2021)
The ability of powered flight in insects facilitated their great evolutionary success allowing them to occupy various ecological niches. Beyond this primary task, wings are often involved in various premating behaviors, such as the generation of courtship songs and the initiation of mating in flight. These specific functions imply special adaptations of wing morphology, as well as sex-specific wing morphologies. Although wing morphology has been extensively studied in Drosophila melanogaster (Meigen, 1830), a comprehensive understanding of developmental plasticity and the impact of sex on wing size and shape plasticity is missing for other Diptera. Therefore, we raised flies of the three Diptera species Drosophila melanogaster, Ceratitis capitata (Wiedemann, 1824) and Musca domestica (Linnaeus, 1758) at different environmental conditions and applied geometric morphometrics to analyze wing shape. Our data showed extensive interspecific differences in wing shape, as well as a clear sexual wing shape dimorphism in all three species. We revealed an impact of different rearing temperatures on wing shape in all three species, which was mostly explained by plasticity in wing size in D. melanogaster. Rearing densities had significant effects on allometric wing shape in D. melanogaster, while no obvious effects were observed for the other two species. Additionally, we do not find evidence for sex-specific response to different rearing conditions in D. melanogaster and C. capitata, while a male-specific impact of different rearing conditions was observed on non-allometric wing shape in M. domestica. Overall, our data strongly suggests that many aspects of wing morphology underly species-specific adaptations and we discuss potential developmental and functional implications of our results.